Eficiencia, igualdad y equidad en la localización de los servicios de salud infantil del Estado de México - Garrocho, Carlos (El Colegio de México A.C., 1993)
This article analyzes the relevance of quantitative models in urban and regional planning by discussing their advantages and limitations and by stressing that these models are not ideologically neutral, especially in their relationship with the theories, values and interests inevitably involved in their design and use. The work proposes a means of utilizing three fundamental criteria of social justice in the analysis of the spatial fairness of the process of decentralization of public pediatrie services in the city of Toluca (state of Mexico). In the empirical analysis, different scenarios for the location of services are simulated using a location-allocation model that includes a spatial interaction model. These options are evaluated in terms of their efficiency, equality and fairness of access.